EFFECT OF SELF DEVELOPMENT PROGRAM AND TRAINING USING VIDEO MODELING METHOD ON DRESSING SKILLS IN CHILDREN WITH INTELLECTUAL DISABILITY - Latifah Susilowati; Anik Rustiyaningsih; Sri Hartini (Belitung Nursing Journal, 2018)
Background: Children with intellectual disability has adaptation function problem, namely self-care skill dressing. Inability to dressing could affect social relationship and dependency with others. The effort to improve self-care skill could be done through self-development program and training using video modeling. Objective: This study was to investigate the effect of self-development program and training using video modeling on dressing skills in intellectual disability children. Methods: This was a quasi-experimental study with pretest posttest control group design. Sixty-two children aged between 6-12 years with intellectual disability were recruited using purposive sampling. Participants were divided into two groups (experimental group=31, control group=31). The experimental group was given training using video modeling in 4 sessions, with each for 50 minutes; and self-development program in 4 sessions, in 50 minutes per each, while control group was given self-development program for 8 sessions, with each for 50 minutes. Observation checklist of dressing skill before and after intervention was adopted from Nursing Outcome Classification in Indonesian version. Data were analyzed using Mann-Whitney to compare posttest score between experimental and control group. Results: The result showed there was a significant difference after intervention between experimental and control group (p=0.041). Eight dressing skills items increased including gets clothing from closet, gets clothing from drawer, puts clothing on upper body, buttons clothing, puts clothing on lower body, uses zipper, uses fastener, and removes clothes from upper body. Conclusion: Self-development program and training using video modeling could increase dressing skills in intellectual disability children aged 6-12 years.